On The Way to a Constitutional Convention for Cyprus - Auer, Andreas (2008)
This working paper aims at presenting, discussing and developing the issue of a constitutional convention as a possible means to initiate a democratic process of autonomous constitution making in Cyprus. Autonomous constitution making means opening a process rather than defining a final product at the outset. Accordingly the goal of this paper is not to provide extensive and comprehensive solutions to important issues of the Cyprus’ problem in general. Instead the objective is to mention the crucial issues that will need to be discussed by the Constitutional Convention for Cyprus. Moreover, this paper outlines what must be the basic legal principles that guide this process and what could be the different steps towards its implementation.